Remotely Sensed Carbonyl Sulfide Constrains Model Estimates of Amazon Primary Productivity. Issue 9 (29th April 2022) - Stinecipher, James R.; Cameron‐Smith, Philip; Kuai, Le; Glatthor, Norbert; Höpfner, Michael; Baker, Ian; Beer, Christian; Bowman, Kevin; Lee, Meemong; Miller, Scot M.; Parazoo, Nicholas; Campbell, J. Elliott
Abstract: Understanding the magnitude of tropical gross primary production (GPP) is critical for carbon cycle modeling and climate projections, but this quantity is poorly constrained at regional scales. Biospheric uptake of carbonyl sulfide (OCS) provides a promising approach to estimating regional GPP. Here, we simulate OCS concentrations driven by surface flux scenarios encompassing a wide range of GPP estimates for the Amazon basin. We compare the model output to satellite retrievals and find a regional GPP estimate of 2375 ± 914 g(C) m −2 yr −1, consistent with previous estimates, including the TRENDY model ensemble range of 1431–3812 g(C) m −2 yr −1 . Plain Language Summary: Carbonyl sulfide is an atmospheric gas that can be used to estimate how much carbon plants assimilate during photosynthesis. One of the most important regions for understanding the carbon cycle is the Amazon rainforest. In order to determine how much carbon is being taken up in the Amazon, we use models of the chemistry and movement of the atmosphere to estimate the uptake of carbonyl sulfide and compare our model output to satellite observations. Our research shows that estimates of Amazonian GPP using carbonyl sulfide uptake are consistent with ecosystem models and other types of observations. This builds confidence in our understanding of carbon uptake in the Amazon, which has major implications for climate predictions. Key Points: Remotely sensed atmospheric carbonyl sulfide can be used to estimate surface processes, namely carbon uptake through photosynthesis Models of carbonyl sulfide indicate that gross primary productivity in the Amazon basin closely follows lower‐productivity ecosystem models High productivity and deep convection over the Amazon enable the surface uptake signal to be picked up in upper tropospheric observations